Recent developments in the Canadian economy: Fall 2024 - Guy Gellatly; Carter McCormack (Economic and Social Reports)
This article provides an integrated summary of recent changes in output, consumer prices, employment, and household finances. It highlights changes in the economic data during the first half of 2024 and into the summer months. The article provides information on how economic conditions have changed as borrowing costs continue to evolve.